The potential role of soil-based interventions in increasing maize yield: a case study of organic and clay-based soil amendments in Central Laos - Mekuria, Wolde (2012)
Soil management practices that produce optimal grain yields while preserving the ecosystem services of agricultural systems are essential in the face climate variability. This study was undertaken in central Laos to investigate the impacts of organic and clay-based soil amendments, and their combination on maize yield. Structured field experiments were established at Veunkham and Naphok sites with 10 treatments each in Randomised Complete Block Design with three replications in 2011. The treatments were rice husk biochar (applied at a rate of 10 t ha-1), Bentonite (10 t ha-1), compost (4 t ha-1), claymanure compost (10 t ha-1), rice husk biochar compost (10 t ha-1), and their combinations. Significantly (p < 0.05) higher maize yield was detected in soils amended with organic and clay-based soil amendments when compared to untreated control. At Veunkham, differences between the control and amended soils in maize yield ranged from 1.5 to 5.8 t ha-1 whereas differences at Naphok were varied between 0.4 and 3.6 t ha-1. The sizeable differences between the control and amended soils in maize yield can be logical consequences of nutrient use efficiency and soil properties improvements resulting from organic and clay-based soil amendments. Interestingly, soils amended with rice husk biochar compost showed maize yield increase of 72 and 45% against soils amended with rice husk biochar at Veunkham and Naphok respectively. Our results demonstrated that organic and clay-based soil amendments have a significant positive effect on the improvement of maize yield and thereby contributes to the improvement of crop water productivity.